Odmiana potoczna - JOLANTA NOCOŃ (Stylistyka)
The colloquial style of Polish is not monolithic; rather, it is characterised by a complex communicative structure and a range of pragmatic conditions, which account for its internal differentiation. As one of the variants of the national language, colloquial Polish is primarily spoken and marked by situationality, interactivity and visuality. Polish stylistics distinguishes between two conceptions of colloquialism rooted in different approaches to style: the functional-communicative and the anthropological- -cultural. The former treats colloquial style as a set of functionally motivated stylistic and linguistic means, and the variety is considered to serve all domains of everyday life. The latter, by contrast, views colloquial style as a way of conceptualising the world, which involves a specific linguistic worldview, experiential framing and a cultural attitude. The colloquial style is positioned as the stylistic core of the Polish language, from which other functional styles evolve. One of the major issues explored in the 21st century is a shift of colloquial forms into official communication, linked to the transformation of modern culture. Numerous extralinguistic and intralinguistic factors contributing to the shift have been identified. Reactions to the spread of colloquialism vary widely, but it is usually regarded either as a process of refreshing modernization of the language or a sign of its degradation, particularly in digital and media contexts.